The effect of fascial manipulation therapy on lower limb spasticity and ankle clonus in stroke patients - Wenyan Li; Xin Liu; Yinghua Wen; Junying Wu; Federico Giordani; Carla Stecco (PAGEPress Publications, 2024)
Lower limb spasticity and clonus are common sequelae after cerebral stroke. An important part of their etiopathogenesis has been related to the peripheral component of spasticity. Rheological properties of the tissues seem to be involved. Several studies highlighted anatomical and functional changes in the connective structures. The fasciae might be implicated in the pathological process. Thus, this study intends to investigate the effect of the Fascial Manipulation (FM) technique on triceps surae in stroke patients through a clinical randomized controlled trial, to provide a reference for clinical treatment of lower limb spasticity and ankle clonus. A total of 40 patients with post-stroke ankle clonus were selected and divided into a control group and an observation group by random number table method, with 20 cases in each group. Both groups received conventional rehabilitation therapy, while the FM group received Fascial Manipulation based on conventional rehabilitation therapy. Before the first treatment and after 3 weeks of treatment, the Comprehensive Spasticity Scale (CSS), the Passive Range Of Motion (PROM), the simplified Fugl-Meyer motor function score (FMA), and the Modified Ashworth Scale (MAS) were used to assess the degree of ankle clonus, ankle passive range of motion, and lower limb motor function of the two groups of patients. Before treatment, there was no statistically significant difference between the control group and the FM group in terms of CSS, PROM, FMA, and MAS of the affected lower limbs (P>0.05). After 3 weeks of treatment, the CSS and MAS of the affected lower limbs in the control group and FM group decreased, while PROM and FMA increased compared to pre-treatment evaluation, with statistically significant differences (P<0.05). Moreover, the FM group showed a statistically significant decrease in CSS and MAS, as well as an increase in PROM and FMA, compared to the control group (P<0.05). Conclusions: Fascial manipulation in addition to conventional therapy can effectively reduce spasticity and ankle clonus in stroke patients in a short time, and improve the passive range of motion of the ankle joint and the function of lower limbs.